2020
DOI: 10.1159/000506081
|View full text |Cite
|
Sign up to set email alerts
|

Lappaconitine Sulfate Inhibits Proliferation and Induces Apoptosis in Human Hepatocellular Carcinoma HepG2 Cells through the Reactive Oxygen Species-Dependent Mitochondrial Pathway

Abstract: Background: Hepatocellular carcinoma (HCC) is the third leading cause of tumor-related deaths in the word. Lappaconitine (LA), a diterpenoid alkaloid, exerts antitumor activities. However, the effects and mechanisms of LA sulfate (LS) on HCC remain unclear. This study evaluated the activities and explored the underlying mechanisms of LS in HCC cell line HepG2 cells. Materials and Methods: The cell viability and proliferation were evaluated using the Cell Counting Kit-8 (CCK-8) and 5-ethynyl-2′-deoxyuridine (Ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It was reported that the hydrobromide salt of lappaconitine could suppress the growth of liver and S180 tumors of mice with inhibition rates of 11.20%∼53.08% and 29.81%∼53.96%, respectively 111,112 and could inhibit the proliferation of human non-small cell lung cancer A549 cells dose dependently by arresting the cells in G1/G0 phase and downregulating the expression of Cyclin E1 ( Table 1 ). 113 Lappaconitine sulfate was also reported to possess antiproliferative activity against various human cancer cell lines: cerical neoplasm (HeLa), 114 liver (HepG2), 115 colon (HT-29), 116 and lung (A549), 117 which might be caused by activation of p38 MAPK-, mitochondrial-, and caspase-mediated apoptosis. In addition, the hydrochloride salt of lappaconitine has been observed for its ability to inhibit proliferation and to induce apoptosis in human colon cancer HCT-116 cells and human liver cancer HepG2 cells via mitochondrial and MAPK pathways.…”
Section: Bioactivitiesmentioning
confidence: 99%
“…It was reported that the hydrobromide salt of lappaconitine could suppress the growth of liver and S180 tumors of mice with inhibition rates of 11.20%∼53.08% and 29.81%∼53.96%, respectively 111,112 and could inhibit the proliferation of human non-small cell lung cancer A549 cells dose dependently by arresting the cells in G1/G0 phase and downregulating the expression of Cyclin E1 ( Table 1 ). 113 Lappaconitine sulfate was also reported to possess antiproliferative activity against various human cancer cell lines: cerical neoplasm (HeLa), 114 liver (HepG2), 115 colon (HT-29), 116 and lung (A549), 117 which might be caused by activation of p38 MAPK-, mitochondrial-, and caspase-mediated apoptosis. In addition, the hydrochloride salt of lappaconitine has been observed for its ability to inhibit proliferation and to induce apoptosis in human colon cancer HCT-116 cells and human liver cancer HepG2 cells via mitochondrial and MAPK pathways.…”
Section: Bioactivitiesmentioning
confidence: 99%
“…Lappaconitine sulfate [ 29 ], lappaconitine hydrobromide, and lappaconitine trifluoroacetate [ 30 ] have exhibited greater solubility in water and pronounced analgesic activity. Salt formation with sulfonic acid was important for antitumor activity [ 31 , 32 ]. A fatty acid chain at the 8-hydroxy group and 13-OH substituent on the diterpenoid core were favorable for the enhancement of the antiproliferative activity [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alperine inhibited Akt-mediated apoptosis, G2/M cell cycle arrest and the proliferation of hepatoma cells [ 28 ]. Lappaconitine sulfate induced apoptosis by mediating the mitochondrial apoptosis pathway [ 29 ]. Bufalin regulated tumor immune microenvironments by Nuclear Factor kappa B (NF-κB) and activates anti-tumor T cell immune response [ 30 ].…”
Section: Introductionmentioning
confidence: 99%